2016
DOI: 10.7727/wimj.2016.526
|View full text |Cite
|
Sign up to set email alerts
|

Acute Paralysis and Neuro-inflammation in Jamaican Children during ZIKV and Dengue Epidemics of 2016

Abstract: Dengue, Chikungunya virus (CHIKV) and Zika virus (ZIKV) are all transmitted by the Aedes aegypti mosquito and are currently circulating in Jamaica. Jamaica has been experiencing a ZIKV epidemic since February 2016. At the University Hospital of the West Indies (UHWI), Kingston, Jamaica, a cluster of five cases of paralysis attributed to neuro-inflammation was noted amongst adolescents admitted to the institution. Three were diagnosed with acute myelitis and one each with acute disseminated encephalomyelitis (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Phylogenetic studies confirmed the arrival of the zika virus (ZIKV) in Jamaica, the Dominican Republic and Haiti, over 9 months before the formal identification of the first clinical case [39,40 ▪▪ ]. Zika has penetrated the Caribbean region (Table 1) [25,39,40 ▪▪ ,41–50,51 ▪▪ ,52–54,55 ▪▪ ,56–65]. The link of zika to congenital zika syndrome (CZS) and Guillain–Barre syndrome (GBS) has been established in the Caribbean, along with other intrauterine pregnancy complications, febrile illnesses, and unusual neurological complications in children (Figs.…”
Section: Zikamentioning
confidence: 89%
“…Phylogenetic studies confirmed the arrival of the zika virus (ZIKV) in Jamaica, the Dominican Republic and Haiti, over 9 months before the formal identification of the first clinical case [39,40 ▪▪ ]. Zika has penetrated the Caribbean region (Table 1) [25,39,40 ▪▪ ,41–50,51 ▪▪ ,52–54,55 ▪▪ ,56–65]. The link of zika to congenital zika syndrome (CZS) and Guillain–Barre syndrome (GBS) has been established in the Caribbean, along with other intrauterine pregnancy complications, febrile illnesses, and unusual neurological complications in children (Figs.…”
Section: Zikamentioning
confidence: 89%
“…In 2014, an epidemic with several thousands of suspected cases of chikungunya virus (CHIKV) infections were reported with an 83.6% seropositivity (9)(10)(11)(12). In 2016, Jamaica experienced its maiden Zika virus (ZIKV) epidemic, when all three arboviruses co-circulated endemically (13)(14)(15)(16). In Cuba, two Ae aegypti mosquito populations became infected with and transmitted DENV-1, ZIKV and CHIKV together, albeit at low rates (17).…”
Section: Introductionmentioning
confidence: 99%
“…The congenital syndrome was also being recognized simultaneously in 0.8% to 2.2% of the newborns in 3 urban public maternity hospitals [ 23 ], with a 15.6% ZIKV immunoglobulin G antibody seroprevalence in pregnancy reported [ 19 ]. Other complications included Guillain-Barré syndrome and varied neurological presentations in children and adults [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ZIKV epidemic in Jamaica occurred in 2016-2017 [20][21][22][23]. National hospital-based surveillance revealed increased annual rates of severe microcephaly from 23.6 per 100,000 live births in 2010 (during the period of DENV outbreaks) to 41.7 per 100,000 live births in 2017 in association with the ZIKV epidemic [14], alongside surveillance reports of the congenital syndrome associated with ZIKV and related fetal brain disruption sequences temporally and spatially related to reported ZIKV cases [14].…”
Section: Introductionmentioning
confidence: 99%